2002
DOI: 10.1620/tjem.197.27
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Color Doppler Ultrasonography Measurements of Full-Term Newborns with Perinatal Asphyxia and Hypoxic Ischemic Encephalopathy in the First 12 Hours of Life and Long-Term Prognosis.

Abstract: The cerebral blood flow velocities (CBFV) of infants with perinatal asphyxia and hypoxic ischemic encephalopathy (HIE) in the first 12 hours of their lives have been the chief focus of our concern in this study. Cerebral ischemia which can develop in the earlier hours of HIE, and the detection and diagnosis of this condition with color Doppler ultrasonography (cD-USG) will be put into discussion. Twenty-three full-term newborn infants who had perinatal asphyxia and HIE together with a control group constitutin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…The study showed that subjects who on the first day were found to have significantly higher Vd values and lower RI values demonstrated severe impairment of mental development (P < 0.05). A number of researchers analyzed associations between blood flow parameters measured via Doppler sonography on the first days of life and long-term outcomes [23,24,[27][28][29]. Some researchers analyzed the significance of blood flow parameters measured during the first 12 h of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that subjects who on the first day were found to have significantly higher Vd values and lower RI values demonstrated severe impairment of mental development (P < 0.05). A number of researchers analyzed associations between blood flow parameters measured via Doppler sonography on the first days of life and long-term outcomes [23,24,[27][28][29]. Some researchers analyzed the significance of blood flow parameters measured during the first 12 h of life.…”
Section: Discussionmentioning
confidence: 99%
“…Kirimi et al investigated the relationship of blood flow parameters registered during the first 12 h after birth with neuromotor and mental development of 1-year-old children. They found that neonates whose Vs and Vd of cerebral blood flow were significantly lower, and R was significantly higher, were found to have cerebral palsy (CP) and impairment of the mental and neuromotor development (P < 0.003) [29]. Ilves et al found that in children with poor outcomes (death or marked disability), blood flow Vs and Vd values in the anterior and medial cerebral arteries recorded 12 AE 2 h after birth were significantly higher than those in the control group (P < 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether 12-MHz ultrasound imaging could be feasible in cerebral vessels and could represent an accurate and reproducible alternative tool to monitor cerebral circulatory changes in rat pups occurring during cerebral ischemia as applied in humans. Indeed, the accuracy of this technique has been validated for comparison transcranial flow velocity and cerebral blood flow during focal ischemia in adult animals (Els et al 1999) and has been used in term human newborns with hypoxic-ischemic encephalopathy (Kirimi et al 2002). This noninvasive method could be repeated allowing longitudinal survey during the whole duration and at each step of the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the measurements of cerebral blood flow velocities (CBFVs) in the anterior cerebral artery (ACA) and middle cerebral artery are valu-able for predicting the neurodevelopmental outcome in infants with intrapartum asphyxia. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, little is known about cerebral blood flow in the basilar artery (BA) in asphyxiated infants. 15 The BA arises from the vertebral arteries and supplies the brain stem with oxygen-rich blood.…”
mentioning
confidence: 99%